Plea Bargaining dalam Sistem Peradilan Pidana di Beberapa Negara - Nella Octaviany Siregar (Universitas Batanghari Jambi, 2019)
Plea Bargaining System is widely interpreted as a statement of guilt of a suspect or defendant. Plea Bargaining practised in many countries that have embraced the Common Law legal system. Plea Bargaining that was developed in the common law